RANCANG BANGUN KNALPOT MENGHASILKAN DUA SUARA PADA KENDARAAN 110 cc - Sabar Pasaribu (JTIK (Jurnal Teknik Informatika Kaputama), 2021)
The purpose of this design is to be able and understand how to build an exhaust on a 110 cc vehicle, the method used in this design is experimentation and literature by carrying out planning activities that see the conditions in the field. So far, we know that the exhaust on a 110 cc motorcycle has only one sound, which in its application we need another exhaust or remodel the kalpot if you want to get a different sound. The problem that will solve this final project is how to design one exhaust that is efficient, simple, economical, and can produce two sounds. There is also the result of planning is to produce a product that is simple, economical and easy to operate.